Rancang Bangun Sistem Proteksi Kebakaran Menggunakan Smoke dan Heat Detector - Zain, Abdul (INTEK: Jurnal Penelitian, 2016)
Abstract—The growth of rapid development in the big cities but without well planning in terms of fire prevention and the things that can cause a fire, for example electrical installations and gas that can either lead to frequent fires in the residential homes. The aim of the study is to prevent fires by detecting the presence of smoke and excessive heat around the house and protect the occurrence of fires that have wide impacts. The outcome of the fire protection design using smoke and heat detector based on microcontroller is to detect both smoke and heat hazards. If there is a danger of smoke or heat, then the system will provide a warning alarm, provide the path to the door emergency evacuation, and provide protection to extinguish the fire before the fire was enlarged.